Plasma Level of MMP-10 May Be a Prognostic Marker in Early Stages of Breast Cancer - Piskór, Barbara Maria (J Clin Med, 2020)
Background: Stromelysins are potential breast cancer biomarkers. The aim of the study was to evaluate if plasma levels of selected metalloproteinases (MMPs) (stromelysin-1 (MMP-3) and stromelysin-10 (MMP-10)) and cancer antigen 15-3 (CA 15-3) used separately and in combination demonstrated diagnostic usefulness in breast cancer (BC). Methods: The study group consisted of 120 patients with BC, while the control group included 40 patients with benign breast cancer and 40 healthy individuals. Concentrations of MMP-3 and MMP-10 were determined by enzyme-linked immunosorbent assay; CA 15-3 was determined by chemiluminescent microparticle immunoassay. Results: In the group of patients with BC, the area under the curve (AUC) was significantly higher for all markers (except MMP-3) and all sets of markers. At the earliest disease stage, only MMP-10 had a significantly higher AUC (AUC = 0.8692, p < 0.001). Moreover, MMP-10 had the highest AUC (0.9166) among parameters tested separately. The highest AUC was observed for the combination of MMP-10 + CA 15-3 and MMP-3 + MMP-10 + CA 15-3 in line with disease progression (stage I 0.8884 and 0.8906, stage II 0.9244 and 0.9308, stages III + IV 0.9919 and 0.9944, respectively, p < 0.001 in all cases). Conclusions: The results suggest that MMP-10 could be a potential marker in early stages of BC. Moreover, plasma concentration of MMP-10 and MMP-3 in combination with CA 15-3 may improve diagnosis of this type of cancer.